Qu'est-ce qu'un parti fondé sur une base religieuse ? Interprétations concurrentes d'une catégorie juridique dans le contexte politique égyptien. (September 2019) - Steuer, Clément
In Egypt, the 'political parties with a religious basis' are explicitly prohibited by law since 1977. However, this ban has had a negligible impact on political life, because administrative jurisprudence has since long diminished its scope, by reducing the question of the religious basis of a party to that of the confession of its members. Nevertheless, the secular opponents of the Islamists have repeatedly claimed, since the constitutionalization of this ban in January 2014, that it should be interpreted more strictly. This article first recalls how the Islamist and secular camps emerged during the political and constitutional struggles of the 2011–2013 era, before examining the competing interpretations of the notion of 'religious party', such as made by the administrative jurisprudence, by supporters of the ban on Islamist parties, and by the Islamists themselves.